Prevalence and pattern of smokeless tobacco use among rural women in Odisha, India - Sussan Baby, Renju; Parida, Rekha; Jacob, Jaison; Mahata, Soumita; A., Sreelekshmi; Roy, Sudipta; Rajak, Sushma; Biswas, Susmita (International Journal Of Community Medicine And Public Health, 2025)
Background: India is one of the world's largest producers and second largest consumers of tobacco, much of it in smokeless forms. It was recognized that SLT use among women is an increasing problem that needs to be addressed through social, behavioural, and policy-level approaches. The study aimed to assess the prevalence of smokeless Tobacco use and to identify the correlates of SLT use among rural women in Odisha. Methods: The research design used for the study was cross-sectional, and a convenient non-probability sampling technique was used to select the subjects. Sociodemographic and tobacco profiles were the tools used to assess the prevalence of the disease. The standardized tool Fagerstrom Nicotine Assessment scale was used to determine the dependency among SLT users. Inferential statistics (chi-square) were used to analyze the data. Results: From the data collected from 234 women in Bhatakhuri village, Odisha, a significant number of women were consuming smokeless tobacco, ie.94(40.17%). The majority of them are low to moderately dependent on SLTs (70%), but it is important to note that 20% of women were significantly reliant on SLT tobacco use. As well as there is a significant correlation between SLT use among women with age and marital status. Conclusions: The study's findings revealed that a substantial number of women were using SLT; its use became part of their lives and is culturally acceptable among women. From the study, we can determine the significant correlation of SLT use with age and marital status.